Design and characterization of a flexible ultra-low-power analog front-end circuit using organic thin-film transistors for wearable electrocardiogram monitoring - Suhad Qasim G. Haddad; Ali Falih Chlloob (International Journal of Electrical and Computer Engineering (IJECE), 2026)
The shift from reactive to proactive healthcare has accelerated the development of flexible, comfortable, and energy-efficient wearable health monitoring systems. This study addresses a critical technological gap: the inherent trade-off between the mechanical flexibility of organic thin-film transistors (OTFTs) and their limited electrical performance (low charge carrier mobility) compared to rigid silicon-based technologies. To overcome this, we outline the system-level design of a fully configurable analog front-end (AFE) utilizing OTFTs for precise electrocardiogram (ECG) measurement. A theoretical transfer-function-based co-design approach is used to balance gain, noise rejection, and power efficiency via high-fidelity MATLAB/Simulink continuous-time simulations. Simulation results demonstrate that the proposed AFE achieves a 40 dB gain, a precise diagnostic bandwidth of 0.5–150 Hz, a common-mode rejection ratio (CMRR) of 65 dB, and an ultra-low power consumption of 33 µW. These metrics strictly align with standard clinical ECG requirements, outperforming current state-of-the-art all-organic architectures primarily in power efficiency. Consequently, the input signal-to-noise ratio (SNR) is significantly enhanced by 24.53 dB (from 8.01 to 32.54 dB). The novelty of this work lies in achieving silicon-like clinical functionality within an all-organic structure at minimal power. This establishes a new benchmark for flexible electronics and paves the way for invisible, skin-like devices for continuous cardiovascular monitoring.